Cybersickness Response among Nursing Students in using Virtual Reality: A Pre-Experimental Study - Noviani Megatami; Iqbal Pramukti; Raini Diah Susanti (Universitas Padjadjaran, 2023)
The rapid growth of information and communication technology, such as virtual reality, affects students’ learning outcomes and their success in providing health services in the future. However, prolonged use of immersive technology could lead to health problems due to repetitive interaction with hardware devices, resulting in a sensory conflict called cybersickness. This study aimed to identify the cybersickness response among nursing students in using virtual reality. This research used a pre-experiment design, and a total of 49 nursing students participated. The Simulator Sickness Questionnaire was used to assess cybersickness and physiological responses. The data were analyzed using the Wilcoxon signed-rank test. The median post-test values for the three components (nausea, oculomotor, disorientation) in cybersickness were 28.7; 45.5; 83.6; and 606.1, respectively. We found statistically significant differences in cybersickness between pre- and post-intervention periods (p < .001). Heart rate and body temperature increased significantly (p < .001; p < .001, respectively), while in both systolic and diastolic blood pressure decreased (p < .001). According to the findings, using VR as an alternative learning media could initiate cybersickness on a certain level. Thus, the physiological response would be different for each participant.